Research note: work to leave, leave to work: motivations of the Jobbymoon takers: evidence from focus group interviews. Issue 4 (4th July 2019) - Yan, Qi York; Hu, Yunhong
ABSTRACT: This research note examines the factors driving the phenomenon of the 'jobbymoon', the practice of undertaking travel between jobs, which has become increasingly popular in recent years. Spawned by the growing transience of job stability, particularly among the millennium generation, the jobbymoon pertinently embodies the blurred if not entangled lines between work and leisure, and therefore is rich in its research implications. Focus group interviews were conducted to identify and evaluate the factors motivating peoples to take jobbymoons. Interviews from focus groups yielded six main categories of motivators, thereby preliminarily revealing the unique relationship between work and leisure as embodied in the jobbymoon. This note claims its research significance in identifying and investigating a special emerging byproduct of work-leisure interactions in the contemporary society, and its findings of the key motivators of the jobbymoon can serve as practical references for product development and marketing efforts for this niche leisure segment.